2021
DOI: 10.1038/s41522-021-00209-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental parameters defining ultra-low biomass bioaerosol analysis

Abstract: Investigation of the microbial ecology of terrestrial, aquatic and atmospheric ecosystems requires specific sampling and analytical technologies, owing to vastly different biomass densities typically encountered. In particular, the ultra-low biomass nature of air presents an inherent analytical challenge that is confounded by temporal fluctuations in community structure. Our ultra-low biomass pipeline advances the field of bioaerosol research by significantly reducing sampling times from days/weeks/months to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…Our study used different flow rates by sample types (i.e., 2.5 L/min for each of the three pumps for indoor samples and 4.0 L/min for each of the two pumps for outdoor samples) to ensure that outdoor air sampling collects similar total volume of air to indoor air sampling with fewer pumps. A study reported that using different sampling flow rates (100, 200, or 300 L/min) caused different particle retention efficiency; 51 however, our study used about 2 orders of magnitude lower flow rates, which would not likely to cause a significant difference in collection efficiency between the indoor and outdoor samples, as found in a study using low flow rates (1 to 4 L/min) 52 . Lastly, the controlled laboratory studies to further examine the effect of disinfection on indoor microbial community composition and how long the effect would last may improve our understanding of effectiveness of disinfection in school environments and its implication for occupants' health.…”
Section: Resultsmentioning
confidence: 99%
“…Our study used different flow rates by sample types (i.e., 2.5 L/min for each of the three pumps for indoor samples and 4.0 L/min for each of the two pumps for outdoor samples) to ensure that outdoor air sampling collects similar total volume of air to indoor air sampling with fewer pumps. A study reported that using different sampling flow rates (100, 200, or 300 L/min) caused different particle retention efficiency; 51 however, our study used about 2 orders of magnitude lower flow rates, which would not likely to cause a significant difference in collection efficiency between the indoor and outdoor samples, as found in a study using low flow rates (1 to 4 L/min) 52 . Lastly, the controlled laboratory studies to further examine the effect of disinfection on indoor microbial community composition and how long the effect would last may improve our understanding of effectiveness of disinfection in school environments and its implication for occupants' health.…”
Section: Resultsmentioning
confidence: 99%
“…Washed solutions from SASS air filters were further processed by filtering through 0.02 mm Anodisc filters (Whatman) using a vacuum manifold (DHI). DNA was then extracted from the Anodisc with the DNeasy PowerWater kit (Qiagen) according to the manufacturer's protocol with modifications to increase DNA yield (Luhung et al, 2021). Sterile swabs, filters and sputum DNA extraction reagents were processed simultaneously as extraction controls to assess the levels of experimental background contamination (Figure S3).…”
Section: Dna Extraction From Clinical and Environmental Samplesmentioning
confidence: 99%
“…As per the manufacturer's specification, the small poresize filter has an efficiency of 90% for particles <0.5 µm with 50 L/ min sampling flowrate, whereas the large pore-size filter has an efficiency of 50% for particles <0.5 µm with 150 L/min sampling flowrate. The air sampler, along with the selected filter media, has been well studied for their use in sampling and analyzing environmental biological [20][21][22] and chemical aerosols. 23 All air samples were duplicated for environmental SARS-CoV-2 test and for culturing (only for positive samples).…”
Section: Air Sampling and Rna Extractionmentioning
confidence: 99%